Contribution of Vocational Madrasah Aliyah in the Growth of Indonesia's Demographic Bonus - Masturin Masturin (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
Demographic bonuses have become the concern of various parties, both government and non-government. Managing the demographic bonus is predicted to contribute to Indonesia's economic conditions positively. In this case, vocational-based Madrasah Aliyah (MA) is required to create competent and competitive working-age human resources significantly. For this reason, this study seeks to answer the contribution of Vocational Madrasah Aliyah (MAK) in welcoming the demographic bonus. This study used a qualitative approach with a case study design, while the informants were determined by purposive sampling. Data collection techniques were in-depth interviews, participant observation, documentation, and focus group discussions. Checking the validity of the data was then carried out by expanding the presence of researchers in the field, deepening observations, triangulation, peer discussions, matching members, transferability, dependability, and confirmability. The study results show that in encouraging the formation of competent working-age human resources, there still needs to be an imbalance in the ideal teacher-student ratio in one region to another, followed by a balance that exceeds government standards. In addition, problems with the implementation of vocational-based Madrasah Aliyah still leave big jobs, including the absence of competency certification for graduates of Vocational Madrasah Aliyah, inadequate madrasah infrastructure, lack of cooperation, and low competency of Vocational Madrasah Aliyah teachers.